A Very Rare Complication After Broncoalveolar Lavage: Pneumothorax - Aydın, Sıyamı; Çakmak, Muharrem; Ak, Sema (My University, 2022)
The frequency of iatrogenic pneumothorax is high in acquired pneumothorax. Bronchoalveolar lavage (BAL) is a method of evaluating materials taken from the tracheobronchial system by bronchoscopy. The complication rate in BAL procedure is below 5%. These complications are pneumonia, temporary alveolar infiltration, bronchospasm, hypoxia and alveolar hemorrhage. Pneumothorax is a very rare complication of BAL. In our study, we aimed to report a very rare case of pneumothorax that developed after BAL.
Keywords: Solunum Sistemi; Anestezi; Kulak; Burun; Boğaz; Radyoloji; Nükleer Tıp; Tıbbi Görüntüleme; Cerrahi